Thermal and phase change process in a branching T-channel under active magnetic field and two rotating inner cylinders: Analysis and predictions by radial basis neural networks - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2023)
Effects of combining the use of a magnetic field with rotating cylinders on the thermal processes and phase transitions in a T-shaped branching channel are examined. In the vertical channel, a PCM-packed bed zone is used, and rotating cylinders are used in both the vertical and horizontal channels. For a range of rotational Reynolds numbers (Rew between -300 and 300), Hartmann numbers (Ha between 0 and 80), and cylinder sizes (Rc1 and Rc2 between 0.01H and 0.2H), investigations are conducted for the effects of coupled forced flow, magnetic field, and rotating cylinder interactions on the efficiency of the thermal and phase change processes. When there is no magnetic field, the entire transition time (TF) may be lowered and at Rew=2000, the TF is reduced by about 42.5% in comparison to a stationary cylinder case (Rew=0). Employing rotations at the fastest speed results in a 26% boost in heat transfer. Thermal performance increases become 181% and 205% at Rew=0 and Rew = -2000, respectively, but the TF value drops by around 31.5% and 17.5% when highest magnetic field strength is considered. When magnetic field and a horizontal channel cylinder are employed, the T-channel system operates most well in terms of phase change and heat transfer process. Fast and accurate predictions of the dynamic aspects of the phase change process are obtained and the full phase transition time is correctly calculated by using the radial basis neural network technique.
Keywords: T-channel; Magnetic field; Phase change material; FEM; Rotating cylinders